Selection of Housekeeping Genes for Transgene Expression Analysis in Eucommia ulmoides Oliver Using Real-Time RT-PCR. (17th March 2010) - Chen, Ren; Gyokusen, Mayumi; Nakazawa, Yoshihisa; Gyokusen, Koichiro
Abstract : In order to select appropriate housekeeping genes for accurate calibration of experimental variations in real-time (RT-) PCR results in transgene expression analysis, particularly with respect to the influence of transgene on stability of endogenous housekeeping gene expression in transgenic plants, we outline a reliable strategy to identify the optimal housekeeping genes from a set of candidates by combining statistical analyses of their (RT-) PCR amplification efficiency, gene expression stability, and transgene influences. We used the strategy to select two genes, ACT α and EF1 α, from 10 candidate housekeeping genes, as the optimal housekeeping genes to evaluate transgenic Eucommia ulmoides Oliver root lines overexpressing IPPI or FPPS1 genes, which are involved in isoprenoid biosynthesis.